Village Resource Development Programme of Village Forest Committees in Bilaspur Forest Circle, Madhya Pradesh - a Case Study - Upadhyaya, J. K. (Indian Forester, 1997)
The dependence of landless and poor masses of the villages in the vicinity of forests for their livelihood, is a well known fact. An integrated approach for the eco-development of this target group is helping to reduce their dependence on the forest. Other groups also being benefited by eco-development programmes and their active Co-operation is being sought for JFM